2019
DOI: 10.15252/embj.2018101032
|View full text |Cite
|
Sign up to set email alerts
|

PP4‐dependent HDAC3 dephosphorylation discriminates between axonal regeneration and regenerative failure

Abstract: The molecular mechanisms discriminating between regenerative failure and success remain elusive. While a regeneration-competent peripheral nerve injury mounts a regenerative gene expression response in bipolar dorsal root ganglia (DRG) sensory neurons, a regeneration-incompetent central spinal cord injury does not. This dichotomic response offers a unique opportunity to investigate the fundamental biological mechanisms underpinning regenerative ability. Following a pharmacological screen with small-molecule in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 37 publications
2
18
0
2
Order By: Relevance
“…The superior regenerative capacity following enriched conditioning might be explained by the intrinsic neuronal transcriptional activation of NOX2 that is further supported by epigenetic mechanisms such as histone acetylation at NOX2 promoters. These epigenetic mechanisms likely allow increased transcriptional activity over prolonged periods of time, as suggested by recent studies where the role of epigenetic regulation in axonal regeneration has been reported 30 , 56 63 . In line with this, we found that enriched conditioning induces an enduring increase in NOX2-dependent redox signaling as suggested by elevated ROS levels up to one week following SCI.…”
Section: Discussionmentioning
confidence: 87%
“…The superior regenerative capacity following enriched conditioning might be explained by the intrinsic neuronal transcriptional activation of NOX2 that is further supported by epigenetic mechanisms such as histone acetylation at NOX2 promoters. These epigenetic mechanisms likely allow increased transcriptional activity over prolonged periods of time, as suggested by recent studies where the role of epigenetic regulation in axonal regeneration has been reported 30 , 56 63 . In line with this, we found that enriched conditioning induces an enduring increase in NOX2-dependent redox signaling as suggested by elevated ROS levels up to one week following SCI.…”
Section: Discussionmentioning
confidence: 87%
“…Injury-induced calcium waves induce the PKCγ-dependent nuclear export of HDAC5, enhancing histone acetylation and gene transcription [53]. More recently, HDAC3 signaling has been recognized as a brake to axonal regeneration: indeed HDAC3 inhibition overcomes the inability of sensory axons to regenerate upon a spinal cord injury [54]. This evidence led to the hypothesis that comparable regulatory mechanisms activating epigenetic regenerative responses may be not functional in the CNS, preventing the gene expression changes essential for efficient axonal re-growth.…”
Section: Epigenetic Regulation Of Axonal Re-growth Programmentioning
confidence: 99%
“…Should the PP2A/4/6 family act at a similar level in adult wildtype animals, there are other means by which its members are known to influence gene expression that may be of particular relevance to aging. Across evolutionarily diverse species, these protein phosphatases regulate histone modification, chromatin organization, and mRNA processing which all undergo significant changes over time [61,[70][71][72][73][74][75][76]. Since we and others find that the PP2A/4/6 phosphatases are important for promoting healthspan, it may be by acting through these pathways that the PP2A/4/6 family modulates the changes in gene expression that are necessary to uphold vitality.…”
Section: Plos Onementioning
confidence: 91%